2016
DOI: 10.1590/1678-4162-8739
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação endoscópica das vias aéreas, do perfil de gases, dos eletrólitos e do equilíbrio ácido-base em equinos submetidos ao treinamento de três tambores

Abstract: [Endoscopic airway, blood gas, electrolytes, and acid-base

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Decrease in pH, HCO 3 and cBase with concomitant reduction in pCO 2 reinforced the occurrence of metabolic acidosis in the present study, corroborating the studies by SILVA et al (2009) who also reported decrease in these parameters in the venous blood of horses after submitting them to maximum exercise on a treadmill. The decrease in these parameters reaffirms the effect of lactic acid diffusion in the blood originating from the muscle cells under the predominance of the anaerobic glucose metabolism, causing lactic acidosis (MARLIN & NANKERVIS, 2002;BARBOSA et al, 2016;LINHARES et al, 2017).…”
Section: Time -------------------------------------------------------mentioning
confidence: 73%
See 2 more Smart Citations
“…Decrease in pH, HCO 3 and cBase with concomitant reduction in pCO 2 reinforced the occurrence of metabolic acidosis in the present study, corroborating the studies by SILVA et al (2009) who also reported decrease in these parameters in the venous blood of horses after submitting them to maximum exercise on a treadmill. The decrease in these parameters reaffirms the effect of lactic acid diffusion in the blood originating from the muscle cells under the predominance of the anaerobic glucose metabolism, causing lactic acidosis (MARLIN & NANKERVIS, 2002;BARBOSA et al, 2016;LINHARES et al, 2017).…”
Section: Time -------------------------------------------------------mentioning
confidence: 73%
“…Exercise intensity and duration determine which is predominant (CAIADO et al, 2011). Equestrian tests, where the exercise of high intensity and short duration, that require rapid energy production and adequate energy consumption to meet the demand of the intense muscular activity, and because it cannot be provided sufficiently by the aerobic pathway, requires the anaerobic pathway (BARBOSA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vaquejada there is a large demand on the horses to exert physical effort, with fast starts, sudden changes in direction and stops, and strength while pulling the steer down (LOPES et al, 2009;MENESES et al, 2014;SOUZA et al, 2017). Thus, as in other Western-type horse contests, the exercise the horse performs in the vaquejada is classified as high intensity short duration, demanding fast energy production and intake to support the big muscular effort, that makes the exercises predominantly anaerobic (BARBOSA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In horse sports where there is high intensity and short duration exercise, the organism intensifies anaerobic mechanisms, mainly the anaerobic glucose (BARBOSA et al, 2016), due to the need for rapid production and uptake of energy to give energetic support to the muscule work (VERMEULEN et al, 2017). Vaquejada is among the sports where anaerobic mechanisms are needed by the horses´ organism.…”
Section: Introductionmentioning
confidence: 99%